The Effect of Leadership Style and Work Ethic on Employee Performance at PT Victory Chingluh Indonesia - Rahmawati, Fitri; Sunarsi, Denok (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
The purpose of this study was to determine the effect of leadership style and work ethic on employee performance at PT Victory Chingluh Indonesia, Tangerang Regency. The method used is quantitative. The sampling technique used saturated sampling, namely 100 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that leadership style has a significant effect on employee performance with a determination coefficient value of 39.3% and the hypothesis test obtained t count> t table or (7.959> 1.984). Work ethic has a significant effect on employee performance with a determination coefficient value of 47.0% and the hypothesis test obtained t count> t table or (9.316> 1.984). Leadership style and work ethic simultaneously have a significant effect on employee performance with a regression equation Y = 5.608 + 0.377X1 + 0.473X2. The coefficient of determination is 58.7%, while the remaining 41.3% is influenced by other variables. The hypothesis test obtained a calculated F value > F table or (68.820 > 2.700).